The Influence of Rural Infrastructure Fund Policy Implementation on Fund Management and Effective Utilization in Garut Regency - Agus Muhammad Barkah (Entrepreneurship Faculty, Universitas Garut, 2025)
This research aims to analyze the influence of rural infrastructure funds policy implementation on funds management and the effectiveness of their usage in Garut Regency. The study employed an explanatory method with evaluation techniques. The population consisted of 421 villages across 42 districts, with 84 villages selected through purposive sampling, using the Headman as the unit of analysis. Data were collected through observation, interviews, questionnaires, and documentation, while hypothesis testing used path analysis. The results show that policy implementation significantly influences funds management (49.93%) and the effectiveness of funds usage (total effect 31.11%). Funds management also has a significant effect on the effectiveness of usage (33.24%). Overall, policy implementation contributes positively to management and effectiveness, with a total influence of 64.36%, while 35.64% is explained by other factors. Direct effects of policy implementation on effectiveness reached 17.80%, with an indirect effect through management of 13.31%. The study also highlights several problems: (1) inadequate quality of village apparatus in policy implementation, (2) lack of effective determination of policy alternatives in funds management, and (3) delays in financial report submissions by many rural governments. These findings suggest the need for capacity-building and stricter monitoring to optimize rural infrastructure funds usage.